Preselection TCR repertoire predicts CD4(+) and CD8(+) T‐cell differentiation state - Hou, Xianliang (Immunology, 2020)
T cells must display diversity regarding both the cell state and T‐cell receptor (TCR) repertoire to provide effective immunity against pathogens; however, the generation and evolution of cellular T‐cell heterogeneity in the adaptive immune system remains unclear. In the present study, a combination of multiplex PCR and immune repertoire sequencing (IR‐seq) was used for a standardized analysis of the TCR β‐chain repertoire of CD4(+) naive, CD4(+) memory, CD8(+) naive and CD8(+) memory T cells. We showed that the T‐cell subsets could be distinguished from each another with regard to the TCR β‐chain (TCR‐β) diversity, CDR3 length distribution and TRBV usage, which could be observed both in the preselection and in the post‐selection repertoire. Moreover, the Dβ‐Jβ and Vβ‐Dβ combination patterns at the initial recombination step, template‐independent insertion of nucleotides and inter‐subset overlap were consistent between the pre‐ and post‐selection repertoires, with a remarkably positive correlation. Taken together, these results support differentiation of the CD4(+) and CD8(+) T‐cell subsets prior to thymic selection, and these differences survived both positive and negative selection. In conclusion, these findings provide deeper insight into the generation and evolution of TCR repertoire generation.